Pharmacogenetics in the treatment of pre-eclampsia: Current findings, challenges and perspectives - Luizon, Marcelo R. [UNESP]; Palei, Ana C.; Cavalli, Ricardo C.; Sandrim, Valeria C. [UNESP] (Taylor & Francis, 2017)
Pre-eclampsia (PE) is defined as pregnancy-induced hypertension and proteinuria, and is a major cause of maternal and perinatal morbidity and mortality. A large subgroup of pregnant women with PE is nonresponsive to antihypertensive drugs, including methyldopa, nifedipine and hydralazine. Pharmacogenomics may help to guide the individualized therapy for this nonresponsive subgroup. However, just a few pharmacogenetic studies examined the effects of genetic polymorphisms on response to antihypertensive drugs in PE, and the criteria of responsiveness used to define responsive or nonresponsive subgroups to antihypertensive therapy should be replicated by others. We review these gene-drugs interactions, novel approaches to pharmacogenomics research and potential novel drugs for PE therapy. Finally, we discuss the challenges and perspectives of pharmacogenetics in the treatment of PE.
Keywords: antihypertensive therapy; genotypes; gestational hypertension; haplotypes; pharmacogenetics; pharmacogenomics; polymorphisms; pre-eclampsia